COVID-19 and mental health in 8 low- and middle-income countries: a prospective cohort study - Aksunger, N; Vernot, C; Littman, R; Voors, M; Meriggi, NF; Abajobir, A; Beber, B; Dai, K; Egger, D; Islam, A; Kelly, J; Kharel, A; et al. (Public Library of Science, 2023)
Background The Coronavirus Disease 2019 (COVID-19) pandemic and associated mitigation policies created a global economic and health crisis of unprecedented depth and scale, raising the estimated prevalence of depression by more than a quarter in high-income countries. Low- and middle-income countries (LMICs) suffered the negative effects on living standards the most severely. However, the consequences of the pandemic for mental health in LMICs have received less attention. Therefore, this study assesses the association between the COVID-19 crisis and mental health in 8 LMICs.